PROTOTYPE SISTEM SMART LOCK DOOR DENGAN TIMER DAN FINGERPRINT SEBAGAI ALAT AUTENTIKASI BERBASIS ARDUINO UNO PADA RUANGAN - Erick Febriyanto; Padeli -; Danang Suprayogi (Jurnal Informatika, 2019)
Security is a matter that must be often ignored by most people and considers it safe, but in fact someone can still lose his valuables. For example in a room where security is often considered good by most people just by locking the door provided, but often people forget to lock the door. Because forgetting to lock the room door causes someone to lose his valuables. The development of technology that has increasingly sophisticated door security systems must keep abreast of the times. Room door security systems that are currently still using conventional methods are considered insecure at this time, even though there is already a CCTV camera that has been used to monitor the room. Therefore the media is used to make a room safer by locking the room with a timer and fingerprint. If the room occupant forgets to lock the door, the automatic door is locked according to the time specified. When in the room the door will not be locked, but if the occupants want to leave the room and forget to lock the room is automatically locked and when you want to open it using only fingerprints. In research conducted by researchers used a qualitative approach, namely by explaining the problem more specifically to the data or facts obtained. For fingerprint data before use, register is done so that fingerprint data is registered on the system and can be used.Keywords : Autentifikasi, Fingerprint, Timer